EU “Mobility” Partnerships: An Initial Assessment of Implementation Dynamics - Reslow, Natasja (2015)
Cooperation with non-EU countries is a central migration policy priority for the EU, and since 2008 eight Mobility Partnerships have been signed. Given the importance attached to this policy area, it is essential that policy-makers understand how EU external migration policy works in practice. However, the literature on the implementation of EU external migration policy is very limited. This article addresses this deficit, by conducting a conceptual assessment of implementation dynamics in the Mobility Partnerships. At this stage in the implementation process, it is not yet possible to assess whether the Mobility Partnerships have contributed to mobility, which is their stated aim. Instead, the literature on implementation is applied in a “backward” fashion, starting with the implementation dynamics at play. The article concludes that standard analytical frameworks for assessing implementation processes will need to be adapted for “new” policy tools featuring elements of flexibility or voluntary participation, in order to accurately capture implementation processes. Future research should adopt a critical, human rights-centred approach to the issue of implementation of EU external migration policy.